Protein, fatty acid, mineral profiles and antioxidant potential of Kupres cheese at different stage of ripening - Zlatan Sarić; Lejla Hozić; Smail Žilić; Tarik Dizdarević; Ivana Sredović-Ignjatović; Bojana Špirović; Mirjana Kresović; Danijel Milinčić; Miroljub Barać (Mljekarstvo, 2022)
Kupres cheese is a traditional Bosnian full-fat hard cheese. This paper deals with the change of protein and fatty acid profiles, mineral content and antioxidant potential during the period of three months of its ripening. Proteolysis was monitored by the electrophoresis of total extracts and water-soluble fractions under reducing conditions, whereas fatty acid profiles were determined by gas chromatography. The mineral content in the ripened cheeses was determined by using methods of Inductively coupled plasma - optical emission spectrometry (ICP-OES) for microelements and Inductively coupled plasma mass spectrometry (ICP-MS) for microelements, respectively. Ripening of Kupres cheese during three months is characterised by a relatively slow proteolysis, especially during the first month and by the increase in desirable fatty acid content. After 30 days of ripening, the WSN/TN and TCA/TN contents increased from 8.23% and 2.25% to 10.15% and 3.59%, respectively. Further, ripening induced higher increase of these parameters and more intensive degradation of the major caseins, especially αs-CN. After three months of ripening, residual level of αs-CN and β-CN was 12.02% and 80.96%, respectively. Three month-old cheese had improved indexes of lipid quality as well as improved reducing power and ability to scavenge free radicals. Ripening affected the content of Ca, P and Na whereas no significant changes of the other macro- and microelements of Kupres cheese were observed.